Indiana University humanities series. - Indiana University (Bloomington, Ind. The University Press, 1939)
Irregular.
Includes also a 1952 ed. of no. 26 published in Dublin by Browne and Nolan.
Title varies: no. 1-43, Indiana University publications. Humanities series.